Callose metabolism and the regulation of cell walls and plasmodesmata during plant mutualistic and pathogenic interactions. (19th December 2022) - German, Liam; Yeshvekar, Richa; Benitez‐Alfonso, Yoselin
Abstract: Cell walls are essential for plant growth and development, providing support and protection from external environments. Callose is a glucan that accumulates in specialized cell wall microdomains including around intercellular pores called plasmodesmata. Despite representing a small percentage of the cell wall (~0.3% in the model plant Arabidopsis thaliana ), callose accumulation regulates important biological processes such as phloem and pollen development, cell division, organ formation, responses to pathogenic invasion and to changes in nutrients and toxic metals in the soil. Callose accumulation modifies cell wall properties and restricts plasmodesmata aperture, affecting the transport of signaling proteins and RNA molecules that regulate plant developmental and environmental responses. Although the importance of callose, at and outside plasmodesmata cell walls, is widely recognized, the underlying mechanisms controlling changes in its synthesis and degradation are still unresolved. In this review, we explore the most recent literature addressing callose metabolism with a focus on the molecular factors affecting callose accumulation in response to mutualistic symbionts and pathogenic elicitors. We discuss commonalities in the signaling pathways, identify research gaps and highlight opportunities to target callose in the improvement of plant responses to beneficial versus pathogenic microbes. Brief summary statement: In this review, we expose our current understanding of the mechanisms that regulate callose accumulation in response to microbes. The aim is to identify research gaps and highlight opportunities to target callose in the improvement of plant responses to beneficial versus pathogenic microbes. Information was missing on the signaling pathways and interactions controlling the expression and activity of callose metabolic enzymes and their relative contribution to the response to microbial symbionts. Knowledge also lacks on the evolutionary and physicomechanical features that selected callose to function in this process. We also highlight opportunities for stronger plant defenses that emerge from priming callose using non‐pathogenic and mutualistic microbes.